2001
DOI: 10.1002/1521-4141(200106)31:6<1935::aid-immu1935>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of TNF and LTα in the host defense againstM. bovis BCG

Abstract: Signaling via TNF receptor type 1 (TNFR1) was shown to be crucial in host defense against the intracellular pathogens L. monocytogenes, M. tuberculosis and M. bovis. Toinvestigate the function of TNF and LTα  in host defense against M. bovis, mice double deficient for TNF and LTα  (TNF / LTα – / –), TNF / LTα – / – mice complemented with a murine LTα  transgene (TNF– / –) and LTα – / – mice were infected with BCG and the ensuing pathology was investigated. Control mice showed a normal host defense with early c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 48 publications
3
56
0
Order By: Relevance
“…This is probably less predominant in M. tuberculosis infection, in which the production of soluble factors results in more efficient response, although the unique presence of Tm TNF without soluble TNF or LT-␣ confers an important protection. Previously, it has been shown that inability to use TNF and LT-␣ in tg mice, TNF Ϫ/Ϫ mice, or LT-␣ Ϫ/Ϫ mice renders animals highly susceptible to M. tuberculosis and BCG infections (23)(24)(25)(26)45). Reduction of immune surveillance in mycobacterial infections leads to the excessive proliferation of intracellular bacteria in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably less predominant in M. tuberculosis infection, in which the production of soluble factors results in more efficient response, although the unique presence of Tm TNF without soluble TNF or LT-␣ confers an important protection. Previously, it has been shown that inability to use TNF and LT-␣ in tg mice, TNF Ϫ/Ϫ mice, or LT-␣ Ϫ/Ϫ mice renders animals highly susceptible to M. tuberculosis and BCG infections (23)(24)(25)(26)45). Reduction of immune surveillance in mycobacterial infections leads to the excessive proliferation of intracellular bacteria in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of TNF with anti-TNF Abs or with soluble TNFR1-Ig fusion protein during M. bovis and M. tuberculosis infections or the absence of a functional TNF gene increased sensitivity by inhibiting macrophage differentiation and the development of well-differentiated granulomas, resulting in mycobacterial overgrowth and rapid animal death (20 -24). Recently, it has been shown that lymphotoxin-␣ (LT-␣) is also required for host defense against BCG and M. tuberculosis infections (25,26). A contribution of cell surface-bound LT-␣ 1 ␤ 2 in protective immunity against BCG infection has been reported (27).…”
mentioning
confidence: 99%
“…In particular, TNF-␣ (10) and lymphotoxin (11) have been demonstrated crucial for granuloma formation and for limiting pathology, and therapies aimed at blocking TNF-␣ do increase the risk of reactivation tuberculosis in humans (12). However, in vitro experiments have failed to demonstrate that TNF-␣ can arm macrophages to kill intracellular bacilli (13).…”
mentioning
confidence: 99%
“…The C allele alters the binding site of the transcriptional repressor (158). The abrogation of the LTA signaling pathway in mice is associated with increased susceptibility to intracellular pathogens (38,116). Attempts to validate LTA SNP associations were made in two additional case-control studies in India (364 patients with leprosy and 371 controls) and Brazil (209 leprosy patients and 192 healthy controls) ( Table 1).…”
Section: Chromosome 6p21: Lymphotoxin-␣mentioning
confidence: 99%